The Effect of Allicin on the Proteome of SARS-CoV-2 Infected Calu-3 Cells - Mösbauer, Kirstin; Fritsch, Verena Nadin; Adrian, Lorenz; Bernhardt, Jörg; Gruhlke, Martin Clemens Horst; Slusarenko, Alan John; Niemeyer, Daniela; Antelmann, Haike (Frontiers in Microbiology, 2021)
Allicin (diallyl thiosulfinate) is the major thiol-reactive organosulfur compound produced by garlic plants (Allium sativum) upon tissue damage. Allicin exerts its strong antimicrobial activity against bacteria and fungi via S-thioallylation of protein thiols and low molecular weight thiols. Here, we investigated the effect of allicin on SARS-CoV-2 infected Vero E6 and Calu-3 cells. Toxicity tests revealed that Calu-3 cells showed greater allicin tolerance, probably due to >4-fold higher GSH levels compared to the very sensitive Vero E6 cells. Exposure of infected Vero E6 and Calu-3 cells to biocompatible allicin doses led to a ~60-70 % decrease of viral RNA and infectious viral particles. Label-free quantitative proteomics was used to investigate the changes in the Calu-3 proteome after SARS-CoV-2 infection and the effect of allicin on the host-virus proteome. SARS-CoV-2 infection of Calu-3 cells caused a strong induction of the antiviral interferon-stimulated gene (ISG) signature, including several antiviral effectors, such as cGAS, Mx1, IFIT, IFIH, IFI16, IFI44, 2’5’OAS and ISG15, pathways of vesicular transport, tight junctions (KIF5A/B/C, OSBPL2, CLTC1, ARHGAP17) and ubiquitin modification (UBE2L3/5), as well as reprogramming of host metabolism, transcription and translation. Allicin treatment of infected Calu-3 cells reduced the expression of IFN signaling pathways and ISG effectors and reverted several host pathways to levels of uninfected cells. Allicin further reduced the abundance of the structural viral proteins N, M, S and ORF3 in the host-virus proteome. In conclusion, our data demonstrate the antiviral and immunomodulatory activity of biocompatible doses of allicin in SARS-CoV-2-infected cell cultures. Future drug research should be directed to exploit the thiol-reactivity of allicin derivatives with increased stability and lower human cell toxicity as antiviral lead compounds. DISCLAIMER: Crushed garlic causes severe damages of epithelial cells in the respiratory tract and the skin. This study in no way suggests that eating, inhalation or insertion of crushed garlic is a viable treatment option for COVID-19 or other respiratory tract infections. We explicitly warn against any form of self-medication with garlic or garlic compounds.